Reynolds averaged and large Eddy computations of flow and heat transfer under round jet impingement - Natarajan, T.; Jewkes, J.; Narayanaswamy, Ramesh; Chung, Y.; Lucey, A. (American Society of Mechanical Engineers (ASME), 2014)
The fluid dynamics and heat transfer characteristics of a turbulent round jet are modelled numerically using Reynolds- Averaged Navier-Stokes (RANS) and Large Eddy Simulation (LES). Meshes with varying degrees of coarseness, with both radial and axial refinements are investigated. Discretization is carried out using the finite volume method. The jet configurations are chosen to enable validation against well-established experimental jet-impingement heat-transfer studies, particularly that of Cooper et al. [1]. The Reynolds number studied is 23000. The height of discharge from the impingement wall is fixed at twice the jet diameter. The work critically examines the effect of Reynolds number, standoff distance and helps to ascertain the relative merits of various turbulence models, by comparing turbulent statistics and the Nusselt number distributions. The present work is carried out as a preliminary validation, in a wider study intended to determine the thermofluidic behaviour of jets impinging upon an oscillating surface.